Husband's social support and subjective well-being among Javanese mothers of children with special needs - Hesdo Celvin Naraha; Sowanya Ardi Prahara; Angelina Dyah Arum Setyaningtyas (INSPIRA: Indonesian Journal of Psychological Research, 2023)
A husband’s social support is one of the factors shaping subjective well-being in mothers who have children with special needs. It is undoubtedly influenced by the cultural values that form the basis of relationships in families of Javanese ethnicity. Therefore, this study looks at the relationship between the husband’s social support and subjective well-being in mothers with children with special needs with a Javanese ethnic background. The sampling technique used was probability sampling with 36 participants of mothers of Javanese ethnicity who had children with special needs in the age range of 1-18 years—data collection using the Mother’s Subjective Well-Being Scale and the Husband’s Social Support Scale. The data analysis technique used is Pearson product-moment correlation. The data analysis shows no relationship between subjective well-being and husband’s social support in mothers of Javanese ethnicity who have children with special needs. The results of this study imply that subjective well-being in mothers with Javanese ethnicity is not related to external factors.